Horizontal Conflict Resolution Related to Belief in Religious Tolerance in Multi-Cultural Society in Indonesia - Muh Aditya Ibrahim; Eri R Hidayat; Halomoan FS Alexandra; Pujo Widodo; Herlina JR Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Social conflicts have the potential to occur in multi-religious societies, especially in multicultural societies, such as Indonesia. One of the factors that causes this to happen is the occurrence of human error in understanding religious texts. The movement of discourse and dialogue among religious adherents has made significant progress. This begins with the awareness that all religious people basically pursue peace, compassion, and love and live happily with their loved ones. Indonesia is a plural country with a diversity of ethnicities, races, cultures, languages ​​and religions. In terms of religion, Indonesia recognizes several religions, namely Islam, Roman Catholicism, Protestantism, Hinduism, Buddhism and Confucianism. These religions have different principles and beliefs. The lack of social order to properly manage these differences has the potential to create conflict. The purpose of this research is to know the ways the conflict resolution of religious tolerance around society in daily life. This research is use qualitative method with descriptive approach. The result of this research is people must know the characteristic of multicultural of Indonesian society to emphasizes that the diversity of patterns of Indonesian society is intended not only for the diversity of ethnic groups but also for the diversity of cultures that exist in society. The existence of this cultural diversity can be seen in mutual respect and tolerance between cultures. Growing The Tolerance as Conflict Resolution to build tolerance each others. Social conflicts are often motivated by differences in characteristics brought by individuals in the realm of society. Success in realizing the noble goal of lasting peace and preventing social conflict between people who in fact are of different religions and cultures, as well as mutual respect and cooperation among various groups of people, ethnicity, language, culture, politics or religion.